Neurologic Complications in Pediatric Allogeneic Stem Cell Transplantation: Analysis of Risk Factors and Outcome. (February 2022) - Turón-Viñas, Eulàlia; Boronat, Susana; Trabazo, Maria; Brió, Sònia; Coca, Elisabet; Morón-Cazalilla, Georgina; Badell, Isabel
Neurologic complications following stem cell transplantation are of utmost importance owing to their high morbimortality. Although many studies have been performed in the adult population, reports in children are scarce. Our objective was to determine the most common neurologic complications in a pediatric population and to analyze possible risk factors for their development. We performed an exploratory retrospective study of neurologic complications in pediatric patients who had allogeneic stem cell transplantation over the last 18 years. We identified 66 neurologic complications in 178 allogeneic stem cell transplantations. The most frequent neurologic complications were those involving the peripheral nervous system and those related to drug toxicity. Survival decreased significantly in the presence of neurologic complications. Multivariate logistic regression analysis showed that independent risk factors for developing neurologic complications were development of chronic extensive graft-vs-host disease requiring treatment, cytomegalovirus reactivation, and central nervous system radiation. Prompt diagnosis and preemptive treatment, if possible, are necessary to avoid long-term sequelae or mortality.